Study of hypothyroidism in pregnancy and it’s fetomaternal outcome: a prospective study at tertiary care hospital - ., Monika; Khoiwal, Susheela; Mourya, Aditi; Sharma, Nisha; Jorwal, Anju (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: Pregnancy is a stress test of maternal thyroid function. The prevalence of thyroid dysfunction in pregnant women is high. This study is aimed to evaluate maternal and fetal outcomes in pregnant women with deranged thyroid profile. The relevance of this study is to document the association of hypothyroidism and its adverse effects on mother and fetus. Methods: All pregnant mother included in the study are subjected to written consent and detailed history taking and fasting blood sample collection. Blood sample collected in fasting state, because lipidemic content in blood interferes with serum thyroid stimulating hormone (TSH) level if blood sample collected in the fed state. Results: A total of 1000 cases were studied. Out of 1000 cases, 71(7.1%) cases found to be hypothyroid. Among them, 14 (19.4%) had overt hypothyroidism and 57 (80.5%) demonstrated subclinical hypothyroidism. Conclusions: Prevalence of subclinical hypothyroidism is 5.6% in 3rd trimester of pregnancy. Anemia, pre-eclampsia, high caesarean rates and neonatal morbidities is significantly associated with hypothyroidism.